Self Assessment Memory Scale (SAMS), a new simple method for evaluating memory function - Kowa, Hisatomo; Uchimura, Maki; Ohashi, Asuka; Hiroe, Mamoru; Ono, Rei (Frontiers in Aging Neuroscience, 2022)
We have developed a new method for easy self-assessment of changes in memory recall impairment, which can be used during the very early stages of dementia. An 8-picture recall and a 16-word regression were assessed, respectively, and the index was calculated by adding up the ratio of correct responses to both tests. A total of 85 subjects including 12 MCI, 8 AD, and 65 older persons with normal cognitive function were evaluated, and the correlation with the WMS-R Logical Memory II score was examined. The results showed that there was a statistically significant correlation between the 8-picture recall (R = 0.872, p < 0.0001) and the index (R = 0.857, p < 0.0001), respectively, with the Logical Memory score. We have named this index as Self Assessment Memory Scale (SAMS), and are now developing a digital tool to enable easy and self-administered evaluation of recall.